Abstracts of the 2012 CSBBCS Annual Meeting. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2012)
The article presents numerous abstracts related 2012 annual Canadian Society for Brain, Behavior and Cognitive Science (CSBBCS) meeting which includes effects of Cue-Size on Global and Local Processing, response methodology matters and effects of delay and instruction specificity on prospective memory.